RETRACTED: BUDAYA WELASAN JAM’IYYAH AHLI THORIQOH QODARIYYAH: ETOS KEAGAMAAN DALAM KULTUR LIVING QUR’AN STUDI KASUS DI DUSUN BAGONGAN, GETASAN, SEMARANG - Neny Muthi’atul Awwaliyah; Mustahidin Malula (Aqlam: Journal of Islam and Plurality, 2019)
RETRACTEDFollowing a rigorous, carefully concerns and considered review of the article published in Aqlam: Journal of Islam and Plurality to article entitled “BUDAYA WELASAN JAM’IYYAH AHLI THORIQOH QODARIYYAH: ETOS KEAGAMAAN DALAM KULTUR LIVING QUR’AN STUDI KASUS DI DUSUN BAGONGAN, GETASAN, SEMARANG” Vol 4, No 1, pp. 66-78, Juni 2019, DOI: http://dx.doi.org/10.30984/ajip.v4i1.907.This paper has been found to be in violation of the  Aqlam: Journal of Islam and Plurality and has been retracted.The article contained redundant material, the editor investigated and found that the paper published in Jurnal Harmoni, Vol. 18, No. 1, pp. 479-489, 2019, DOI: https://doi.org/10.32488/harmoni.v18i1.343.The document and its content has been removed from Aqlam: Journal of Islam and Plurality and reasonable effort should be made to remove all references to this article.